Different Euler Bases

Calculus Level 5

n = 1 N 1 ( n ) + N 0 ( n ) n ( 2 n + 1 ) \large \sum_{n=1}^\infty \dfrac{N_1(n)+ N_0(n)}{n(2n+1)}

Let N 0 ( x ) N_0(x) and N 1 ( x ) N_1(x) denote the number of zeros and ones, respectively, when x x is written in base two .

If the value of the series above is equal to a γ a\gamma , where γ \gamma denotes the Euler-Mascheroni constant , find a a .


The answer is 2.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Mark Hennings
Apr 11, 2016

The number N 0 ( n ) + N 1 ( n ) N_0(n) + N_1(n) is just the number of digits in the binary expansion of n n . Thus N 0 ( n ) + N 1 ( n ) = m N_0(n) + N_1(n) = m for 2 m 1 n < 2 m 2^{m-1} \le n < 2^m for any m 1 m \ge 1 . Thus the sum is S = m = 1 n = 2 m 1 2 m 1 m n ( 2 n + 1 ) = m = 1 2 m n = 2 m 1 2 m 1 ( 1 2 n 1 2 n + 1 ) = m = 1 2 m n = 2 m 2 m + 1 1 ( 1 ) n n = m = 1 2 m { 2 n = 2 m 1 2 m 1 1 2 n n = 2 m 2 m + 1 1 1 n } = m = 1 2 m { 2 n = 1 2 m 1 n 1 n = 1 2 m 1 1 n 1 n = 1 2 m + 1 1 n 1 } = m = 1 2 m { 2 n = 1 2 m n 1 n = 1 2 m 1 n 1 n = 1 2 m + 1 n 1 + 2 m 1 } = 2 + m = 1 2 m { 2 [ S 2 m + ln 2 m ] [ S 2 m 1 + ln 2 m 1 ] [ S 2 m + 1 + ln 2 m + 1 ] } = 2 + m = 1 2 m [ 2 S 2 m S 2 m 1 S 2 m + 1 ] \begin{array}{rcl} \mathcal{S} & = & \displaystyle \sum_{m=1}^\infty \sum_{n=2^{m-1}}^{2^m-1} \frac{m}{n(2n+1)} \; = \; \sum_{m=1}^\infty 2m \sum_{n=2^{m-1}}^{2^m-1}\left(\frac{1}{2n} - \frac{1}{2n+1}\right) \\ & = & \displaystyle \sum_{m=1}^\infty 2m \sum_{n=2^m}^{2^{m+1}-1} \frac{(-1)^n}{n} \; = \; \sum_{m=1}^\infty 2m \left\{ 2\sum_{n=2^{m-1}}^{2^m-1} \frac{1}{2n} -\sum_{n=2^m}^{2^{m+1}-1} \frac{1}{n}\right\} \\ & = & \displaystyle \sum_{m=1}^\infty 2m\left\{ 2\sum_{n=1}^{2^m-1} n^{-1} - \sum_{n=1}^{2^{m-1}-1} n^{-1} - \sum_{n=1}^{2^{m+1}-1}n^{-1}\right\} \\ & = & \displaystyle \sum_{m=1}^\infty 2m\left\{ 2\sum_{n=1}^{2^m} n^{-1} - \sum_{n=1}^{2^{m-1}} n^{-1} - \sum_{n=1}^{2^{m+1}}n^{-1} + 2^{-m-1}\right\} \\ & = & \displaystyle 2 + \sum_{m=1}^\infty 2m\left\{ 2\big[ S_{2^m} + \ln 2^m\big] - \big[S^{2^{m-1}} + \ln 2^{m-1}\big] - \big[S_{2^{m+1}} + \ln2^{m+1}\big]\right\} \\ & = & \displaystyle 2 + \sum_{m=1}^\infty 2m\big[ 2S_{2^m} - S_{2^{m-1}} - S_{2^{m+1}}\big] \end{array} where S n = m = 1 n m 1 ln n , S_n \; = \; \sum_{m=1}^n m^{-1} - \ln n \;, noting that S n = γ + o ( n 1 ) S_n \,=\, \gamma + o(n^{-1}) as n n \to \infty . But then S = 2 + lim M m = 1 M 2 m [ 2 S 2 m S 2 m 1 S 2 m + 1 ] = 2 + lim M { m = 1 M 4 m S 2 m m = 0 M 1 2 ( m + 1 ) S 2 m m = 2 M + 1 2 ( m 1 ) S 2 m } = lim M [ ( 2 M + 2 ) S 2 M 2 M S 2 M + 1 ] = 2 γ + lim M [ ( 2 M + 2 ) ( S 2 M γ ) 2 M ( S 2 M + 1 γ ) ] = 2 γ \begin{array}{rcl} \mathcal{S} & = & \displaystyle 2 + \lim_{M\to\infty} \sum_{m=1}^M 2m\big[ 2S_{2^m} - S_{2^{m-1}} - S_{2^{m+1}}\big] \\ & = & \displaystyle 2 + \lim_{M \to \infty} \left\{ \sum_{m=1}^M 4m S_{2^m} - \sum_{m=0}^{M-1}2(m+1)S_{2^m} - \sum_{m=2}^{M+1}2(m-1)S_{2^m}\right\} \\ & = & \displaystyle \lim_{M \to \infty} \big[(2M+2)S_{2^M} - 2MS_{2^{M+1}}\big] \\ & = & \displaystyle 2\gamma + \lim_{M\to\infty}\big[(2M+2)(S_{2^M}-\gamma) - 2M(S_{2^{M+1}}-\gamma)\big] \\ & = & 2\gamma \end{array} making the answer 2 \boxed{2} ..

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...